Mesa redonda: posturas encontradas En el arbitraje internacional - Remón, Jesús (2017)
Are the criti cisms to investment arbitrati on valid?. Is the annulment acti on an indispensable mechanism?. Can the acts of ius imperium of the States be submitted to arbitration?.This round table respond to each of these questi ons by addressing many controversial issues in itnernati onal arbitration.